The Application of Cobit 5.0 Framework to Measure Capability of Information and Technology Governance and Management Processes - Fajri, T. Irfan; Nuryanto, Uli Wildan; Najmi, Muazziss; Suryadi, Dikky; Octiva, Cut Susan (Jurnal Informasi dan Teknologi, 2024)
This study examines the measurement of Information Technology governance and management capability levels using Cobit 5.0. Researchers collected data through questionnaires and interviews. Data processing from questionnaires and interviews can reveal the company's current level. In the EDM domain, the company scored very high in the process that addresses information technology risk optimization. Regular evaluation of business processes is crucial to create alignment and deal with possible risks. To move up to level two, companies must identify and understand the impact of the risks that arise. Companies should enhance their information technology services and security within the domain, perform audits, and report current and future risks. In this domain, companies must identify service capacity, predict future needs, and be ready to face sudden changes. In the DSS domain, companies need to have information system analysis experts conduct training for their staff, identify availability and service problems, and test the ability of their systems to move up to level two.